Effects of two different injury prevention resistance exercise protocols on the hamstring torque-angle relationship: a randomized controlled trial - Naclerio, F.; Larumbe-Zabala, E.; Monajati, A.; Goss-Sampson, M. (Research in Sports Medicine, 2015)
The effects of two different 6-week lower body injury prevention programmes on knee muscle torque-angle relationship were examined in soccer players. Thirty-two men were randomly assigned to three groups: hamstring-eccentric (ECC) (n = 11), unstable-squatting (UNS) (n = 11), and control (n = 10). Intervention groups performed three training sessions per week using only three ECC or UNS exercises, respectively. Maximal peak knee flexion torque was measured at 35°, 45°, 60°, 80°, 90°, and 100°, pre- and post-intervention. Peak torque increased at 35° (P = 0.034, Cohen`s d = 0.67) and 45° (P = 0.004, Cohen`s d = 0.96) in the ECC group, and at 60° (P = 0.024, Cohen`s d = 1.16), 80° (P = 0.018, Cohen`s d = 1.21), and 90° (P = 0.001, Cohen`s d = 1.38) in the UNS group. As these specific modifications might respectively and differentially protect athletes against hamstring and knee-joint injuries, the integration of both types of exercises should be considered when designing injury prevention programmes for soccer players.